A mismatch between morphological and molecular data in lineages of Enteromius (Cypriniformes: Cyprinidae) from the Lowa basin (East Democratic Republic of the Congo: DRC) with the description of a new species. Issue 1 (31st December 2022) - Kisekelwa, Tchalondawa; Snoeks, Jos; Decru, Eva; Schedel, Frederic B. D.; Isumbisho, Mwapu; Vreven, Emmanuel
Abstract : Six populations of morphologically similar Enteromius specimens with a weakly thickened and serrated dorsal spine from the Lowa basin were investigated using an integrative approach including qualitative characters, multivariate morphometrics, and DNA analyses (mtCOI and ncMyh6). These populations are nested within the COI lineage of the E. miolepis species-complex, but differ from all known Enteromius species from the Congo basin, by their dorsal spine morphology, colour pattern, and scale pattern at the dorsal-fin base. In addition, they represent two distinct COI lineages (genetic distance: 5.6–6.1%), with four populations forming a single well-supported lineage described as a new species, Enteromius radari sp. nov. The two remaining populations are sister to the E. miolepis lineage from the Itimbiri. The incongruent position of these two populations in the COI tree may point to past introgressive hybridization events, incomplete lineage sorting, or recent speciation. Analysis of a ncDNA marker (Myh6) did not provide more information due to its slow mutation rate. These results are indicative for introgression or mtDNA capture and provide the first report for such an evolutionary event in Enteromius from the Congo basin. http://zoobank.org/urn:lsid:zoobank.org:pub:D2263E5B-D403-404C-B66C-852215ED100C